4d(d+2)-2d=3(2+d)

Simple and best practice solution for 4d(d+2)-2d=3(2+d) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4d(d+2)-2d=3(2+d) equation:


Simplifying
4d(d + 2) + -2d = 3(2 + d)

Reorder the terms:
4d(2 + d) + -2d = 3(2 + d)
(2 * 4d + d * 4d) + -2d = 3(2 + d)
(8d + 4d2) + -2d = 3(2 + d)

Reorder the terms:
8d + -2d + 4d2 = 3(2 + d)

Combine like terms: 8d + -2d = 6d
6d + 4d2 = 3(2 + d)
6d + 4d2 = (2 * 3 + d * 3)
6d + 4d2 = (6 + 3d)

Solving
6d + 4d2 = 6 + 3d

Solving for variable 'd'.

Reorder the terms:
-6 + 6d + -3d + 4d2 = 6 + 3d + -6 + -3d

Combine like terms: 6d + -3d = 3d
-6 + 3d + 4d2 = 6 + 3d + -6 + -3d

Reorder the terms:
-6 + 3d + 4d2 = 6 + -6 + 3d + -3d

Combine like terms: 6 + -6 = 0
-6 + 3d + 4d2 = 0 + 3d + -3d
-6 + 3d + 4d2 = 3d + -3d

Combine like terms: 3d + -3d = 0
-6 + 3d + 4d2 = 0

Begin completing the square.  Divide all terms by
4 the coefficient of the squared term: 

Divide each side by '4'.
-1.5 + 0.75d + d2 = 0

Move the constant term to the right:

Add '1.5' to each side of the equation.
-1.5 + 0.75d + 1.5 + d2 = 0 + 1.5

Reorder the terms:
-1.5 + 1.5 + 0.75d + d2 = 0 + 1.5

Combine like terms: -1.5 + 1.5 = 0.0
0.0 + 0.75d + d2 = 0 + 1.5
0.75d + d2 = 0 + 1.5

Combine like terms: 0 + 1.5 = 1.5
0.75d + d2 = 1.5

The d term is 0.75d.  Take half its coefficient (0.375).
Square it (0.140625) and add it to both sides.

Add '0.140625' to each side of the equation.
0.75d + 0.140625 + d2 = 1.5 + 0.140625

Reorder the terms:
0.140625 + 0.75d + d2 = 1.5 + 0.140625

Combine like terms: 1.5 + 0.140625 = 1.640625
0.140625 + 0.75d + d2 = 1.640625

Factor a perfect square on the left side:
(d + 0.375)(d + 0.375) = 1.640625

Calculate the square root of the right side: 1.280868846

Break this problem into two subproblems by setting 
(d + 0.375) equal to 1.280868846 and -1.280868846.

Subproblem 1

d + 0.375 = 1.280868846 Simplifying d + 0.375 = 1.280868846 Reorder the terms: 0.375 + d = 1.280868846 Solving 0.375 + d = 1.280868846 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-0.375' to each side of the equation. 0.375 + -0.375 + d = 1.280868846 + -0.375 Combine like terms: 0.375 + -0.375 = 0.000 0.000 + d = 1.280868846 + -0.375 d = 1.280868846 + -0.375 Combine like terms: 1.280868846 + -0.375 = 0.905868846 d = 0.905868846 Simplifying d = 0.905868846

Subproblem 2

d + 0.375 = -1.280868846 Simplifying d + 0.375 = -1.280868846 Reorder the terms: 0.375 + d = -1.280868846 Solving 0.375 + d = -1.280868846 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-0.375' to each side of the equation. 0.375 + -0.375 + d = -1.280868846 + -0.375 Combine like terms: 0.375 + -0.375 = 0.000 0.000 + d = -1.280868846 + -0.375 d = -1.280868846 + -0.375 Combine like terms: -1.280868846 + -0.375 = -1.655868846 d = -1.655868846 Simplifying d = -1.655868846

Solution

The solution to the problem is based on the solutions from the subproblems. d = {0.905868846, -1.655868846}

See similar equations:

| 3+5x=9+3x | | 1/2(2x-4)=3x+5/6 | | [3v-2]/5=4 | | 9y-5-6y+1=0 | | 35-7x=9(3x+3) | | (4x^2+3)(x-4)(x+4)=0 | | 8y+13=5y-5 | | (y+.33)(y-.33)= | | [1-6n]+3=46 | | 5x^2-6x+5= | | 0.1(x+250)=5,000 | | 8x^5+26x^3-24x=0 | | x=1056-.1x | | 7(z-5)+1=2-3(2z-1) | | 2x+6x-14=22 | | [4x+4]=28 | | 12+x=-3x(4-x) | | 6(2x-5)=12 | | -118-3x=77+12x | | 12x+x=-3x(4-x) | | [-7x+4]=18 | | 2(6x+2)=-(2x-10) | | C=3ab | | (x+0.2)(x-0.2)= | | -11a-17a+11a+10a+-2a=18 | | 4x-37=x+35 | | 1/2+3/2=3 | | C=3pieab | | 20x-16=4x+ | | -9x+13=5 | | 18t-13t-t-3t=12 | | 3+2z-1=7z+7-42 |

Equations solver categories